1993
DOI: 10.1002/ijc.2910540104
|View full text |Cite
|
Sign up to set email alerts
|

Absence of HTLV‐I infection among seronegative subjects in an endemic area of Japan

Abstract: To examine the prevalence of infection by human T-cell leukemia virus type I (HTLV-I) among seronegative subjects, healthy subjects on Tsushima Island, Japan, where the infection is endemic, were evaluated. A total of 209 healthy adults were examined for HTLV-I provirus in peripheral blood mononuclear cells by the polymerase chain reaction (PCR), as well as for anti-HTLV-I antibodies by the particle agglutination (PA) method, the enzyme-linked immunosorbent assay (ELISA) and by immunofluorescence analysis (IF)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 27 publications
0
3
0
1
Order By: Relevance
“…19) A validation study also showed that the presence of HTLV-I proviral DNA in peripheral blood mononuclear cells, as detected by the polymerase chain reaction method, was closely correlated with serum HTLV-I antibodies tested by the IF method. 20) Thus, we concluded that any misclassification of HTLV-I carrier status would have been very small and did not pose a problem in this study. Information on other variables Blood pressure, body mass index, and serum total cholesterol levels were measured at the time of AHS health examinations.…”
Section: Methodsmentioning
confidence: 83%
“…19) A validation study also showed that the presence of HTLV-I proviral DNA in peripheral blood mononuclear cells, as detected by the polymerase chain reaction method, was closely correlated with serum HTLV-I antibodies tested by the IF method. 20) Thus, we concluded that any misclassification of HTLV-I carrier status would have been very small and did not pose a problem in this study. Information on other variables Blood pressure, body mass index, and serum total cholesterol levels were measured at the time of AHS health examinations.…”
Section: Methodsmentioning
confidence: 83%
“…HTLV‐1 infection has been shown to be associated with the development of HAID and cases have been reported in HTLV‐1 endemic regions. Japan has the highest prevalence of HTLV‐1 , and in spite of this, HAID is rarely reported in this population, whilst various other skin eruptions of prognostic significance are seen in approximately 50% of Japanese ATLL patients . This indicates that other factors such as host, environmental and genetic factors may play a causative role.…”
Section: Genetics Host and Environmental Factorsmentioning
confidence: 99%
“…Thereafter, it was disseminated to the new world via the transatlantic slave trade and possibly through mongoloid migration across the land bridge Beringia during the Palaeolithic era . The virus is endemic in Japan, the Caribbean, South America and Africa . Approximately 10–20 million people are infected worldwide and only 5–10% suffer from the disease .…”
Section: Introductionmentioning
confidence: 99%
“…Resultados semelhantes foram encontrados em outros estudos similares (d' Auriol et al, 1990;van der Ryst et al, 1996). No entanto, trabalhos pesquisando sequências genômicas do HTLV-1 em soronegativos sem doenças neurológicas não encontraram discrepância entre os resultados obtidos por PCR e por exames de pesquisa de anticorpo (Nakashima et al, 1990;Kinoshita et al, 1993). Embora a literatura não seja unânime, a infecção falha pelo HTLV-1 onde não há produção de anticorpos, porém sequências como a tax estão presentes parece ser uma possibilidade e uma interessante alternativa para a presença desse gene nas glândulas salivares de pessoas com SS e HTLV-1 negativas.…”
Section: Cd4unclassified